2017
DOI: 10.3390/biom7010019
|View full text |Cite
|
Sign up to set email alerts
|

Common Chemical Inductors of Replication Stress: Focus on Cell‐Based Studies

Abstract: DNA replication is a highly demanding process regarding the energy and material supply and must be precisely regulated, involving multiple cellular feedbacks. The slowing down or stalling of DNA synthesis and/or replication forks is referred to as replication stress (RS). Owing to the complexity and requirements of replication, a plethora of factors may interfere and challenge the genome stability, cell survival or affect the whole organism. This review outlines chemical compounds that are known inducers of RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 324 publications
(363 reference statements)
7
76
0
2
Order By: Relevance
“…To further assess whether TIAR prevents mitotic entry in the presence of unreplicated DNA, we induced mild replication stress by treatment with a low dose (0.4 μM) of aphidicolin (APH), an inhibitor of DNA polymerases. At this concentration, cells are affected in S‐phase specifically, and replication is perturbed only partially . Quantification of p‐H3‐positive cells showed that the G2/M checkpoint was strongly activated after 8 h in control cells, whereas TIAR kd cells activated the checkpoint only partially and entered mitosis prematurely (Fig A).…”
Section: Resultsmentioning
confidence: 94%
“…To further assess whether TIAR prevents mitotic entry in the presence of unreplicated DNA, we induced mild replication stress by treatment with a low dose (0.4 μM) of aphidicolin (APH), an inhibitor of DNA polymerases. At this concentration, cells are affected in S‐phase specifically, and replication is perturbed only partially . Quantification of p‐H3‐positive cells showed that the G2/M checkpoint was strongly activated after 8 h in control cells, whereas TIAR kd cells activated the checkpoint only partially and entered mitosis prematurely (Fig A).…”
Section: Resultsmentioning
confidence: 94%
“…In recent studies, we have shown that 7a treatment further increases S phase arrest of the cell cycle over hydroxyurea (HU) treatment [13], which is a pure inducer of replication stressdependent S phase arrest [60,61]. In the present study, HCT116 cells were treated with 25 mM of 5-FU for 24 h, then with 20 mM of 7a or 7b for additional 8 h (Fig.…”
Section: Compound 7b Abrogates S Phase Arrest Of Hct116 Cellsmentioning
confidence: 68%
“…It is well-established that ATR-mediated Chk1 phosphorylation at S317P and S345P plays a critical role in DNA replication, DNA repair, S-G 2 /M phase checkpoint control [62], and has been the target for cancer therapy [63], It has been also shown that the inhibition of Chk1(S317P) and Chk1(S296P) abrogates Sphase progression [64,65]. Since 7b abrogates S phase arrest, we determined the phosphorylation level of Chk1 after treatment with 7b either alone or in combination with HU, a pure inducer of S phase arrest [60,61]. The experimental protocol is described in Fig.…”
Section: Compound 7b Blocks Hu-induced Phosphorylation Of Chk1 In Hctmentioning
confidence: 99%
“…4A and 4B). These treatments seem to act through a common pathway: induction of DDR [45]. Specifically, HU, which inhibits the incorporation of nucleotides by interfering with the enzyme ribonucleotide reductase [46], and APH, which interferes with DNA replication by inhibiting DNA polymerases α, ε and d [47], are both commonly used to induce replication fork stalling that leads to ATR/ATM activation.…”
Section: Discussionmentioning
confidence: 99%